ANALISIS COMPETITIVE ADVANTAGE DAN POTENSI WISATA KAWASAN AGROWISATA (STUDI PADA KAWASAN WISATA CIWIDEY) - Rani Sukmadewi; Herwan Abdul Muhyi; Arianis Chan; Pratami Wulan Tresna (POLITEKNIK LP3I JAKARTA, 2024)
Competitive strength in the tourism sector is a crucial factor for destinations. This study aims to analyze the competitive advantage and tourism potential of the agrotourism area in Ciwidey, Indonesia. By utilizing existing models and frameworks to evaluate tourism competitiveness, this research identifies key determinants that contribute to the competitive advantage of specific tourism destinations. The research methods include interviews, observations, documentation, and focus group discussions. Data were collected from three villages in Ciwidey District, namely Lebakmuncang, Panundaan, and Rawa Bogo, during the period of December 2023 to February 2024. The results indicate that agrotourism and culture are the main potentials to be developed. This research provides valuable insights for policymakers, tourism stakeholders, and local communities to support sustainable development and tourism expansion in the region.